Miles Davis the collected artwork - Davis, Miles 1926-1991 (Insight Ed., 2013)
Throughout the 1980s, Davis studied regularly with New York painter Jo Gelbard, developing a distinct graphic style. Incorporating bright colors and geometric shapes, his art is reminiscent of work by Pablo Picasso as well as African tribal art
Foreword / Quincy Jones -- Introduction / Scott Gutterman -- Part 1: drawings / reflection by Vince Wilburn Jr. -- Part 2: paintings / reflection by Erin Davis -- The styles of Miles / Scott Gutterman -- Afterword / Cheryl Davis
Keywords: Davis, Miles; Davis, Miles / Catalogs; Davis, Miles -- 1926-1991; Painters / United States / Catalogs; Musicians as artists / United States / Catalogs; African American painters / Catalogs; Zeichnung; Malerei; USA; Katalog